(3GdOQ GdoefXe aj RjGQI GdLHd GdoebWes - (3ehab GdOjf CHj eMeO YHO GdQMef Hf CHj GdMQe ecj Hf YKeGf GdTGQYjs; (3dHjO Hf QHjYI Hf eGdc, CHh Ybjd GdYGeQj,J (B41 (3g` s
(3ChdgG (B:s
(3gPG cJGH PcQJ ajg aVGFd RjGQI GdbHhQ hBOGHgG hPcQJ ajg CjVkG aVGFd LHd GdebWe hCOhjJg hbHhQ GdUGdMjf GdJi ai SaMg s
(3BNQgG (B:s
(3hcfJ CYOg hdOG hgPG B NQ eG GfJgi Edjg GdcJGH s
(3GfXQ GjVG Qbe (B469s
(3Qbe (B798 (3JGQjNs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs